DEVELOPMENT OF AN ENCYCLOPEDIA OF ANGIOSPERMS FOUND IN THE SCHOOL ENVIRONMENT AS A SOURCE FOR LEARNING MATERIALS PLANTAE OF CLASS X STUDENTS OF SMAN 4 SUNGAI RAYA - Pramuda, Adi; Trisianawati, Eka; Oktavianti, Syarifah Dwi (Universitas Lancang Kuning, 2024)
Effective, interesting and enjoyable learning requires tools to support successful learning which are interrelated, namely teaching, learning activities and learning resources. Learning resources are a very important factor to support success in the learning process. The aim of this research is to determine the validity, practicality and effectiveness of the angiosperm encyclopedia found in the school environment as a source of learning plant material for class X students at SMAN 4 Sungai Raya. The research method used was Research and Development (R&D) with the 1974 Thiagarajan 4D research design (Define, Design, Develop and Disseminate). The data collection techniques used are measurement techniques and indirect communication techniques, instruments used include validation sheets, response questionnaires, and pretest posttest questions. The sample in the research used a Purposive Sampling technique, namely with a class X B population. The data analysis technique used was a test of validity, practicality and effectiveness. The validity results in this study were 88.38%, practicality 96.02%, the effectiveness obtained was an N-Gain value of 0.69 in the medium category.